Consumer preferences for rice in Liberia: Some preliminary results - Twine, E.; Arouna, A.; Aboudou, R.; Ndindeng, S. (2024)
The study investigates preference for rice quality attributes among Liberian consumers and seeks to understand their valuation of biofortified rice. It employs cross-sectional data obtained from a July 2024 survey of 543 randomly selected consumers from the counties of Bong, Lafia, Margibi and Nimba. Preliminary results indicate that the most important quality characteristics are stickiness (as reported by 23% of respondents), slow digestibility (15%), hard grain (13%), fine grain (11%), swelling capacity (11%), non-sticky when cooked (7%) and doughy (7%). On price - quality tradeoff, most households (59%) consider good quality to be more important than price/affordability (41%). 54% of households consume both local and imported rice, while 46% consume only imported rice. The most popular type of rice is parboiled imported rice (95%), followed by non-parboiled local rice (17%), and parboiled local rice (11%). The most important factors by which imported rice is recognized are price (40%), cleanliness (25%) and branding (23%). 59% of households prefer imported rice to local rice. Preference for imported over local rice is because of the former’s cleanliness (80%), superior taste (68%), greater swelling capacity (61%), aroma (53%), ease of cooking (53%), long grains (48%) and fine grains (41%). Nearly all households are unaware of biofortified crops including rice. However, given knowledge of biofortified crops, 91% of households would buy it if available on the market. Households would pay on average US$ 1.13/kg of milled biofortified rice (cf. current national average of US$ 0.8/kg). Implications for breeding and competitiveness of local rice are discussed.